Trans-cinnamaldehyde ameliorates neuroinflammation-mediated synaptic plasticity and memory impairment by blocking TLR4/MyD88/MAPKs pathway in global cerebral ischemia - Xinjuan Liu; Zhiyuan Lu; Gaiying He; Waimao Gao; Kaifan Hu; Jie Pan; Yan Zhao; Xingyu Wang; Guang Yang; Ying Xu (Brain Research Bulletin, 2025)
Global cerebral ischemia (GCI), a severe form of ischemic stroke, leads to significant cognitive and neurological deficits, with neuroinflammation playing a central role in its pathophysiology. Trans-cinnamaldehyde (TCA), derived from Cinnamomum cassia (L.), has demonstrated anti-inflammatory and neuroprotective effects, but its role in GCI remains unclear. This study investigated whether TCA could ameliorate cognitive impairments in GCI rats by targeting neuroinflammation. A GCI rat model was established using the Pulsinelli four-vessel occlusion method. Behavioral tests, including the open field test, novel object recognition, and water maze, were conducted to assess cognitive function, while long-term potentiation (LTP) analysis was used to evaluate synaptic plasticity. Histological methods, including immunofluorescence and immunohistochemistry, assessed neuronal integrity and microglial activation in the hippocampus. Molecular techniques quantified synaptic protein expression, pro-inflammatory cytokines and TLR4/MyD88/MAPKs pathway activation in GCI rats and primary microglia. We found that TCA significantly improved learning and memory, as demonstrated by behavioral tests, and enhanced synaptic plasticity in GCI rats. Histological analysis revealed that TCA preserved neuronal morphology and inhibited microglial activation. Molecular assays confirmed that TCA reduced synaptic protein overexpression, decreased pro-inflammatory cytokine (IL-6, IL-1β, TNF-α) levels, and suppressed TLR4/MyD88/MAPKs pathway activation in GCI rats or primary microglia induced by LPS. In conclusion, TCA shows neuroprotective potential in GCI by modulating synaptic damage and microglia activation mediated by the TLR4/MyD88/MAPKs pathway and may serve as a therapeutic strategy for ischemic brain injury and related neurodegenerative conditions.